Solar Proton Transport Within an ICRU Sphere Surrounded by a Complex Shield: Ray-trace Geometry - Slaba, Tony C.; Wilson, John W.; Badavi, Francis F.; Reddell, Brandon D.; Bahadori, Amir A. (My University, 2014)
The computationally efficient HZETRN code has been used in recent trade studies for lunar and Martian exploration and is currently being used in the engineering development of the next generation of space vehicles, habitats, and extra vehicular activity equipment. A new version (3DHZETRN) capable of transporting High charge (Z) and Energy (HZE) and light ions (including neutrons) under space-like boundary conditions with enhanced neutron and light ion propagation is under development. In the present report, new algorithms for light ion and neutron propagation with well-defined convergence criteria in 3D objects is developed and tested against Monte Carlo simulations to verify the solution methodology. The code will be available through the software system, OLTARIS, for shield design and validation and provides a basis for personal computer software capable of space shield analysis and optimization.
Citation: Slaba TC, Wilson JW, Badavi FF, Reddell BD, and Bahadori AA 2015 Solar Proton Transport within an ICRU Sphere Surrounded by a Complex Shield: Ray-Trace Geometry NASA/TP-2015-218994 NASA Langley Research Center: Hampton, VA http://ntrs.nasa.gov/search.jsp?R=20160002213
Keywords: Solar Protons; Radiation Shielding; Ray Tracing; Computational Geometry; Combinatorial Analysis; Three Dimensional Models